Distribution of Oral Mucosal Lesions Among Patients Visiting Qamar Dental Hospital in Karachi - Ram, Krishni; Ali, Iqra; Khalid, Tabia Fatima; Aziz, Javaria; Aziz, Javaria; Fatima, Mahnoor; Saleem, Esha; Ali, Anosha; Khero, Rabail (Journal of Neonatal Surgery, 2025)
Background: Oral mucosal lesions (OMLs) are an important clinical and public health concern due to their association with high-risk habits, potential malignant transformation, and impact on quality of life. South Asia, particularly Pakistan, carries a disproportionate burden, driven largely by smokeless tobacco, areca nut (Areca catechu), and betel quid consumption. Objective: This study aimed to determine the prevalence and distribution of OMLs among patients visiting Qamar Dental Hospital in Karachi and to assess associations with demographic and behavioral risk factors. Methods: A cross-sectional study was conducted from February 2024 to February 2025, enrolling 1,236 patients. Comprehensive intraoral examinations were performed using World Health Organization (WHO) criteria, with incisional biopsy and histopathological examination in clinically ambiguous cases. Data were analyzed for prevalence, age- and gender-specific distribution, and associations with risk factors. Results: OMLs were diagnosed in 384 patients (31.1%). The most frequent lesions were oral leukoplakia (18.5%), oral submucous fibrosis (14.6%), oral lichen planus (12.0%), traumatic ulcerations (11.5%), and oral candidiasis (10.4%). Males had a higher prevalence of leukoplakia and submucous fibrosis, while females more often presented with oral lichen planus and candidiasis. Patients aged ≥40 years exhibited significantly higher rates of potentially malignant disorders (PMDs). Tobacco chewing, areca nut/betel quid use, and cigarette smoking were strongly associated with OMLs (p < 0.05). Conclusion: The results highlight a significant load of OMLs in Karachi, where with a high prevalence of potentially malignant disorders that are associated with high-risk preventable habits. Dental clinics form an important point of opportunistic screening, behavioral counseling, and early therapeutic intervention, thus averting the risk of developing malignant transformation into oral squamous cell carcinoma and enhancing overall oral health outcomes